(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the theoretical-methodological foundations of the development of bioethical culture among students is an urgent task, this historical process and historical factors, causes, problematic processes of the emergence of bioethics, and the connection between human value and pedagogy are relevant for any era.